A comprehensive review of experimental models and induction protocols for avian necrotic enteritis over the past 2 decades - Shamshirgaran, Mohammad Ali; Golchin, Mehdi (Frontiers in Veterinary Science, 2024)
Necrotic enteritis (NE) is a severe gastrointestinal disease that poses a significant threat to the poultry industry. It leads to progressive damage to the small intestine, reduced performance, increased mortality rates, and substantial economic losses. With the removal of antimicrobial agents from chicken feed, there is an urgent need to find alternative approaches for NE control.Various approaches, including vaccination, prebiotics, probiotics, and plant-derived products, have been utilized to address NE in poultry management. To evaluate the efficacy of these preventive measures against NE, successful induction of NE is crucial to observe effects of these approaches in related studies. This study presents a comprehensive overview of the methods and approaches utilized for NE reproduction in related studies from 2004 to 2023. These considerations are the careful selection of a virulent C. perfringens strain, preparation of challenge inoculum, choice of time and the route for challenge inoculum administration, and utilization of one or more predisposing factors to increase the rate of NE occurrence in birds under experiment. We also reviewed the different systems used for lesion scoring of NE-challenged birds. By gaining clarity on these fundamental parameters, researchers can make informed decisions regarding the selection of the most appropriate NE experimental design in their respective studies.